Peran kepemimpinan transformasional dan penerapan disiplin terhadap kinerja guru melalui kepuasan kerja sebagai variabel intervening pada sekolah dasar kecamatan Jombang kota Cilegon - Prasetyo, Eko; Yusuf, Furtasan Ali; Jayadi, B. Herawan; Suparmoko, Muhamad; Sari, Gema Ika (Borobudur Educational Review, 2025)
In the educational environment, schools have a critical role in determining the quality and effectiveness of the teaching and learning process. Transformational leadership that focuses on motivation and innovation is considered capable of responding more effectively to the challenges of modern education. In Cilegon City, there is an observation that performance has a direct impact on teacher discipline and mentality, which in turn affects the quality of teaching by teachers. Several factors that can improve performance are transformational leadership and work discipline. This research aims to analyze the influence of transformational leadership and the application of discipline on teacher performance with job satisfaction as an intervening variable in elementary schools in Jombang District, Cilegon City. In an era of increasingly complex education, the role of transformational leadership is crucial in building a work culture that is inspiring and oriented towards improving the quality of teaching. The application of discipline is also considered an important factor in shaping teacher behavior and work ethic. This research uses a quantitative approach with a survey method, involving a number of teachers as respondents. Data were analyzed using Structural Equation Modeling (SEM) techniques to test the relationship between variables. The research results show that transformational leadership and the application of discipline have a positive and significant influence on teacher performance. In addition, job satisfaction is proven to be an intervening variable that strengthens the influence of transformational and disciplinary leadership on teacher performance. These findings indicate that efforts to improve teacher performance do not only depend on aspects of leadership and discipline, but must also consider the level of job satisfaction felt by teachers. The practical implication of this research is the importance of school principals adopting a transformational leadership style and strengthening the application of discipline in order to increase job satisfaction and overall teacher performance